The Effect of Using Microsoft Visio Application on Drawing Learning Outcomes of TIT XI Class Students - Hariyanto, Inge Yellia Adinda Agus (Jurnal Pembangunan Pendidikan: Fondasi dan Aplikasi, 2024)
This study was conducted to determine [1] the learning outcomes in the form of drawing skills before and after the use of Microsoft Visio application and [2] the effect of using Microsoft Visio application on drawing learning outcomes in class XI TITL at SMKN 1 Driyorej. The research design used was pre-experimental design in the form of one group pretest-posttes. The population of this study included class XI TITL as many as 31 students who learned Electrical Power Installation. This research uses sampling type. The results of this study [1] the mean pretest value obtained was 69.03 and the mean posttest value was 83.1. Obtained the results oftcount = 17.47> ttable = 2.04. meaning that H0is not approved and H1 can be approved, so it is known that there are differences in drawing learning outcomes before and after using the Microsoft Vision application. Meanwhile, in hypothesis testing, the value oftcount = 6.42 > ttable = 2.04 was obtained, meaning that H0 isnot approved and H1 can be approved, so it is known that there is a significant positive effect of using the Microsoft Visio application on the learning outcomes of drawing students in class XI TITL Electrical Power Installation subjects at SMKN 1 Driyorej.